2012
DOI: 10.1111/ene.12037
|View full text |Cite
|
Sign up to set email alerts
|

Risk prediction of very early recurrence, death and progression after acute ischaemic stroke

Abstract: RRE-90 bears high potential to not only predict early recurrence but also death and progression after ischaemic stroke. ABCD(2) appears to be useful to predict risk of death and progression. These findings have relevant clinical implications for early triage of patients being admitted to stroke units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 35 publications
0
25
1
Order By: Relevance
“…[8,9] The frequency of neurological deterioration in this singlecenter study was 15.4%, which was higher than that of a retrospective study which assessed deteriorations within the first two days [10] and lower than those of two prospective studies (35% and 37%, respectively). [11,12] The studies for early neurological deterioration in non- thrombolyzed patients were found to have frequencies between 13 to 37% [13][14][15][16][17] Our patients with neurological progression had worse NIHSS scores on discharge, compared to non-progressive patients (8 vs 3.7), while the NIHSS scores were not different on admission between these two groups.…”
Section: Discussioncontrasting
confidence: 66%
“…[8,9] The frequency of neurological deterioration in this singlecenter study was 15.4%, which was higher than that of a retrospective study which assessed deteriorations within the first two days [10] and lower than those of two prospective studies (35% and 37%, respectively). [11,12] The studies for early neurological deterioration in non- thrombolyzed patients were found to have frequencies between 13 to 37% [13][14][15][16][17] Our patients with neurological progression had worse NIHSS scores on discharge, compared to non-progressive patients (8 vs 3.7), while the NIHSS scores were not different on admission between these two groups.…”
Section: Discussioncontrasting
confidence: 66%
“…These findings were robust to sensitivity analyses [see Additional file 1]. One evaluation study for the RRE-90 score estimated an AUROCC of 0.72 (95% CI 0.64 to 0.80) [52] and another of the LiLAC score estimated an AUROCC of 0.65 (95% CI 0.61 to 0.70) [50]. We identified two evaluations of the ABCD2 score [48,52,53].…”
Section: Resultsmentioning
confidence: 64%
“…We identified four additional evaluations among the model development studies [30,37,39,41] giving fifteen evaluation cohorts: five evaluations of the ESRS [29,37,43-45]; three of the SPI-II [41,46,47]; five head-to-head comparisons of the ESRS and the SPI-II [30,39,48-51]; one head-to-head comparison of the ESRS and the RRE-90 [52]; and one comparing the ESRS, the SPI-II and the LiLAC models [50]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third International Stroke Trial (IST-3) showed some benefit in selected patients within 6 hours from symptom onset and demonstrated benefit in elderly patients over 80 years of age (previously excluded from treatment) and those with severe stroke. 23 Owing to a significant risk of early recurrence of stroke (>3%), 24 all patients should start aspirin of 100 to 300 mg immediately after the diagnosis cardiac causes, and lipid abnormalities), thus together accounting for 90% of strokes. Those 10 modifiable risk factors contribute the most to stroke risk and should be targeted in clinical practice.…”
mentioning
confidence: 99%